2021
DOI: 10.1007/s00018-021-04049-5
|View full text |Cite
|
Sign up to set email alerts
|

Activation of neutral sphingomyelinase 2 through hyperglycemia contributes to endothelial apoptosis via vesicle-bound intercellular transfer of ceramides

Abstract: Background Pro-apoptotic and pro-inflammatory ceramides are crucially involved in atherosclerotic plaque development. Local cellular ceramide accumulation mediates endothelial apoptosis, especially in type 2 diabetes mellitus, which is a major cardiovascular risk factor. In recent years, large extracellular vesicles (lEVs) have been identified as an important means of intercellular communication and as regulators of cardiovascular health and disease. A potential role for lEVs as vehicles for cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…33,34 In the context of extracellular vesicles, our group showed that hyperglycemia-induced activation of NSM-2 promotes endothelial apoptosis through the intercellular transfer of ceramides via extracellular vesicles. 35…”
Section: Ceramide Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 In the context of extracellular vesicles, our group showed that hyperglycemia-induced activation of NSM-2 promotes endothelial apoptosis through the intercellular transfer of ceramides via extracellular vesicles. 35…”
Section: Ceramide Metabolismmentioning
confidence: 99%
“…In this context, hyperglycemia has been associated with endothelial ceramide accumulation. 35,54 While in the early years of ceramide research, the induction of cellular apoptosis was thought to be the leading cause of ceramide-associated cellular injury, 55 this has been challenged, as increases in cellular ceramide levels have been shown to occur only at later stages in apoptosis. 56,57 In macrophages, endothelial cells, hepatocytes, and cancerous cell lines, such as MCF7 (Michigan Cancer Foundation-7) breast cancer cells, NSM-2 and related ceramide was found to mediate cellular effects of TNF (tumor necrosis factor)-α receptor.…”
Section: Cellular Mechanisms Of Action Of Ceramides In Cvdmentioning
confidence: 99%
“…Furthermore, ceramide accumulation through increased de novo ceramide production may dictate endothelial cell fate and injury [ 197 ]. Endothelial cell apoptosis in response to hyperglycemia has been related to the intercellular transfer of high concentrations of C 16:0 ceramides in large extracellular vesicles derived from nSMase2-dependent sphingomyelin hydrolysis, thereby causing endothelial dysfunction in obesity and diabetes [ 310 ]. By correlating C 16:0 ceramide levels in thoracic adipose tissue and circulation with the deregulation of the vascular redox state and inflammation in human atherosclerotic patients, together with complementary experiments on human tissue ex vivo and primary cultured cells in vitro, it has been suggested that adipose-tissue-derived C 16:0 ceramides increase the risk of cardiovascular death by acting on endothelial cells to reduce vasodilation, induce inflammation, and promote oxidative stress via eNOS uncoupling [ 299 ].…”
Section: Relevant Tissues Of Ceramide Metabolism and Action In Obesitymentioning
confidence: 99%
“…Similarly, C16-ceramides drive apoptosis in human coronary artery endothelial cells (HCAECs). Under hyperglycemic conditions, Zietzer and colleagues showed that C16-ceramides dominated HCAEC-derived large extracellular vesicles (lEVs), the latter of which triggered HCAEC apoptosis [ 62 ]. Inhibition of neutral sphingomyelinase 2 (nSMase2), significantly reduced C16-ceramides (as well as other less dominant ceramide species) in lEVs, which resulted in the abrogation of hyperglycemic-induced apoptosis in HCAECs [ 62 ].…”
Section: Are Ceramides Responsible For Certain Fatty Acid-induced Er ...mentioning
confidence: 99%
“…As mentioned earlier, the acyl length of ceramides is linked to its toxicity, with C16- and C18-ceramides being notorious in the development of various diseases [ 29 , 32 , 41 , 62 ]. Saddoughi et al reported that I2PP2A preferentially binds to C18-ceramides over C14-, C16-, C20-, C22-, and C24-ceramides [ 75 ], suggesting that C18-ceramides are a relatively more potent inhibitor of Akt compared to other ceramides.…”
Section: Mechanisms Underpinning Ceramide-mediated Apoptosismentioning
confidence: 99%